2019
DOI: 10.1080/26410397.2019.1610277
|View full text |Cite|
|
Sign up to set email alerts
|

Humanised childbirth: the status of emotional support of women in rural Bangladesh

Abstract: The World Health Organization has recently set standards emphasising the importance of emotional support during birth for improving the quality of maternal and newborn healthcare in facilities. In this study, we explore the emotional support status of women during birth in rural Bangladesh. A cross-sectional household survey of 1367 women was administered in 2018 in Brahmanbaria district. Outcomes of interest included: presence of a companion of choice; mobility; intake of fluids and food; and position of choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…24 There is not a standardised approach used to ascertain the presence, duration and timing of labour companionship which presents challenges for facilitating comparability between studies. 25 For example, Afulani et al 26 used both a Likert scale and binary yes/no question to ascertain the presence or absence of labour companionship in Kenya among women up to 9 weeks post partum (78.0%, 26.0% and 88.0% during labour, birth and after birth, respectively), Udofia and Akwaowo 27 designed semistructured questionnaire for use among women up to 8 weeks post partum (69.4% during childbirth in Uyo, Nigeria) and Craymah et al 20 used a self-designed survey for women up to 12 weeks post partum and only assessed male labour companionship in Anomabo, Ghana (44.0% during birth). Due to the use of a single, standardised tool across four countries, we were able to establish how labour companionship characteristics varied across countries in our study.…”
Section: Discussionmentioning
confidence: 99%
“…24 There is not a standardised approach used to ascertain the presence, duration and timing of labour companionship which presents challenges for facilitating comparability between studies. 25 For example, Afulani et al 26 used both a Likert scale and binary yes/no question to ascertain the presence or absence of labour companionship in Kenya among women up to 9 weeks post partum (78.0%, 26.0% and 88.0% during labour, birth and after birth, respectively), Udofia and Akwaowo 27 designed semistructured questionnaire for use among women up to 8 weeks post partum (69.4% during childbirth in Uyo, Nigeria) and Craymah et al 20 used a self-designed survey for women up to 12 weeks post partum and only assessed male labour companionship in Anomabo, Ghana (44.0% during birth). Due to the use of a single, standardised tool across four countries, we were able to establish how labour companionship characteristics varied across countries in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Male partners' presence as supporters is generally less common, for example it is not allowed in parts of the Middle East [42]. Attendance by male partners at facility births was around 14% in urban Nigeria and about 20% in rural Bangladesh, with the most commonly reported reason for their absence being staff refusal [43,44]. Higher rates have been observed at a university hospital in Nigeria and in India [45,46].…”
Section: Theory Of Changementioning
confidence: 99%
“…I shall refer to these factors as the 'supply' of opportunities for men to engage and of a welcoming environment. Surveys show that even where the presence of the male partner at birth is not the norm, such as in Nigeria, Bangladesh and China, many women wish that their partner could or would be with them during labour or birth [41,43,44]. Studies from Ghana and Kenya have shown that women who are wealthier, employed or with higher education are more likely to want and be allowed to have support in labour [39,48].…”
Section: Theory Of Changementioning
confidence: 99%
“…Although we do not have speci c data, other studies conducted in similar settings reported that such social support was provided by a female member of the woman's family, and sometimes a female person outside of the family (38). This is not surprising, given that pregnancy and childbirth are often considered women-centric life transitions (39).…”
Section: Discussionmentioning
confidence: 75%